2017
DOI: 10.1177/0954008317709892
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of phthalonitrile resins promoted by melamine

Abstract: Melamine, which has a unique structure and is known as an important raw material, was first employed as a curing agent to promote the curing reaction of phthalonitrile monomer 1,3-bis(3,4-dicyanophenoxy)benzene. Rheometric measurements and differential scanning calorimetry showed that the blends exhibited wide processing windows (*80 C). The thermal properties of the final cured polymers were monitored by thermogravimetric analysis, and the results revealed that the polymers had outstanding thermal stabilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…BHP (16 g, 50.79 mmol) was dissolved in DMF (100 mL) containing anhydrous K 2 CO 3 (14.05 g, 101.66 mmol). 32 The compound was stirred under N 2 atmosphere at 90°C for 1 h. Subsequently, 4-nitrophthalonitrile (17.59 g, 101.60 mmol) was slowly added into the three-necked flask, and the compound reacted for an additional 6 h. Lastly, the resultant brown compound was slowly decanted into 1.5 L of cooled deionized water to obtain the target material, BDSP, after cooling to ambient temperature. The sediment was acquired through filtration, then washed with alcohol for 48 h at 50°C, and finally dried in an oven to collect the pure sample of BDSP.…”
Section: Methodsmentioning
confidence: 99%
“…BHP (16 g, 50.79 mmol) was dissolved in DMF (100 mL) containing anhydrous K 2 CO 3 (14.05 g, 101.66 mmol). 32 The compound was stirred under N 2 atmosphere at 90°C for 1 h. Subsequently, 4-nitrophthalonitrile (17.59 g, 101.60 mmol) was slowly added into the three-necked flask, and the compound reacted for an additional 6 h. Lastly, the resultant brown compound was slowly decanted into 1.5 L of cooled deionized water to obtain the target material, BDSP, after cooling to ambient temperature. The sediment was acquired through filtration, then washed with alcohol for 48 h at 50°C, and finally dried in an oven to collect the pure sample of BDSP.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, certain researchers have made great efforts to introduce trifunctional structures into PN resins , . A novel alkyl‐center trisphenolic‐based PN thermoset and tris‐PN thermosets with amino‐1,3,5‐triazine structures were synthesized with excellent thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…And we found that a complex curing agent can effectively improve the curing process. As mentioned above, the melamine showed good performance as a curing agent for phthalonitrile resin attributed to its unique structure. However, melamine will sublimate above 300°C, and the curing temperature of the resin is above 350°C at present.…”
Section: Introductionmentioning
confidence: 91%
“…But it was found that the introduction of Cu to the polymer led to the deterioration of long‐term oxidative stability. Recently, melamine, which has a unique structure, was first employed as a curing agent to promote the curing reaction of phthalonitrile resin, the curing system exhibited wide processing window, and the resins had outstanding thermal stabilities. And it should be noted that the curing reaction was conducted in an inert atmosphere (nitrogen and argon) and required a long curing time (30 h).…”
Section: Introductionmentioning
confidence: 99%